Social and Environmental Factors Influencing COVID-19 Transmission and Mortalities in Developing and Developed Nations - Soheli Chowdhury; Majeedul Chowdhury (Epidemiology, Biostatistics and Public Health)
Background: The study sought to establish environmental and social factors that influenced the transmission and mortalities of COVID-19 in developing and developed nations. The factors that were assessed included temperature, average age of the population, urbanization, population density, and percentage of old-aged people in the population. The dependent variables were COVID-19 transmission and COVID-19-related deaths. Methods: The study employed a pragmatism research philosophy. It also relied on a deductive research approach and a descriptive research design. It adopted a mixed-method approach as it used both qualitative and quantitative data. It was a cross-sectional study, given its data measurement at a particular point in time. Data was analyzed and presented using descriptive techniques. Results: Statistical analyses were conducted to quantify the relationships between various factors and COVID-19 outcomes. A Kendall’s Tau test revealed a robust negative correlation between COVID-19 cases and temperature (Tb = -0.560, p<0.005). This result was further confirmed by Spearman’s rank correlation, showing a strong negative correlation with r(13) = -0.684, p<0.007. Similarly, a strong negative correlation was observed between COVID-19 deaths and average annual temperature using both Kendall’s Tau (Tb = -0.495, p<0.014) and Spearman’s rank correlation (r(13) = -0.648, p<0.012). Age emerged as a significant factor, with a strong positive correlation found between age and both COVID-19 infections (Tb = 0.516, p<0.010; r(13) = 0.670, p<0.009) and COVID-19-related mortalities (r(13) = 0.516, p<0.029). Urbanization was also positively correlated with COVID-19 infections (Tb = 0.530, p<0.008; r(13) = 0.640, p<0.014) and COVID-19 deaths (Tb = 0.398, p<0.048; r(13) = 0.561, p<0.037). Interestingly, no significant correlation was found between population density and COVID-19 infections or deaths in both developed and developing countries, as evidenced by Kendall’s Tau (TB = 0.331, p<0.1; Tb = 0.133, p<0.511) and Spearman’s rank correlation (r(13) = 0.425, p<0.130; r(13) = 0.161, p<0.583), respectively. Moreover, the percentage of elderly individuals in a country exhibited a strong positive correlation with both COVID-19 infections (Tb = 0.464, p<0.021; r(13) = 0.642, p<0.013) and COVID-19-related deaths (r(13) = 0.541, p<0.046). Conclusion: The study focused on social, demographic, and environmental factors influencing COVID-19 incidence and mortality in developing and developed nations. The study highlights significant COVID-19 transmission and mortality disparities between developed and developing countries. Developed countries exhibited higher infection and mortality rates, coupled with elevated death rates per million and infection rates per million, as compared to their developing counterparts. The research identified a correlation between lower average annual temperatures and increased mortality in developed countries. Contrary to this, high average annual temperatures were associated with a decline in COVID-19 infections. Moreover, developed countries, characterized by higher urbanization levels, population densities, and percentages of aged individuals, experienced elevated COVID-19 infection rates. The study also unveiled a positive correlation between age and COVID-19 infections, with developed countries hosting significantly older populations than their developing counterparts. However, population density did not clearly correlate with COVID-19 infections or deaths.